School, Symbolic Violence, and Religious Experience of Aboge Youth - Mochammad Zaka Ardiansyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This article reveals various forms of approaches taken by religious education teachers and religious materials in public and religious schools and madrasa teachers to Aboge youth. The teacher’s strategy for managing diversity leaves a variety of problems because not all teachers are aware that their response to Aboge youth is a violation of religious freedom. Although there are teachers who commit symbolic violence with repressive-intimidating patterns, there is a dialogic pattern developed by a teacher in madrasas. Although it is also equally aimed at leading students’ logic that the Aboge calendar method is irrelevant, the strategy makes students mindfully convert their beliefs without blaming their family’s Aboge beliefs and being accommodating Aboge. Even though it seems democratic, MTs Maulana Utama has indicated that it has not carried out a policy of recognition of minorities, so there is a risk of violation of religious freedom if there are other non-Aboge minority students with a different ideological and school of fiqh background. Even though it seems democratic, MTs Maulana Utama has indicated that it has not carried out a policy of recognition of minorities, so there is a risk of violation of religious freedom if there are other non-Aboge minority students with a different ideological and school of fiqh background.